Accessing Kant : a relaxed introduction to the Critique of pure reason - Rosenberg, Jay F. (OUP E-Books., 2005)
Ideal for advanced students coming to terms with this difficult work, this introduction to one of the masterpieces of philosophy will also be of interest to professional philosophers.